Human Cytomegalovirus infection in Pregnancy- a neglected public health problem. - Abdullahi Sani Gadama (Sokoto Journal of Medical Laboratory Science)
Human Cytomegalovirus (HCMV) is one of the most successful human parasites. It survives comfortably in its human host in latent form and could be reactivated under favoring circumstances. It is transmitted both vertically from mother to foetus and horizontally from one person to another. It is the most common congenital cause of mental retardation and auditory disorders in children. Infection with HCMV in immunocompetent individual is usually beneath the threshold of clinical recognition but it can cause serious disease in developing foetus and immunocompromised. HCMV infection has worldwide endemic distribution with no seasonal variation. Prevalence is higher in communities with low socioeconomic status and low level of personal hygiene. Infection with HCMV present in virtually every population that has been tested with prevalence among women of reproductive age ranging from 45% in developed countries to 100% in developing nations. Evidence has shown that HCMV Primary infection in pregnant women of developed nations is associated with high risk of transmission to the developing foetus. With the high prevalence of HCMV in sub-Saharan Africa, it is possible for non-primary HCMV infection to account for the main burden of Congenital HCMV infection in these areas. The risk of transmission to the developing foetus is even higher in pregnant women with HCMV/HIV co-infection. Awareness and knowledge of HCMV is often hidden in a lacuna, as a result, no intervention policy for the prevention and control of HCMV across nations worldwide. It is important therefore, to initiate a worldwide awareness campaign on HCMV infection and its consequences for the purpose of prevention and control since there is yet to be consensus by the scientific societies on the treatment options.